(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This study aims to explain the relationship between international accounting and financial reporting “standards” and financial stability, and its impact on the cost of financing with common shares for a sample of banks listed on the Iraqi Stock Exchange. Our research sample included (9) banks, using the dummy index to express international accounting and financial reporting standards as an independent variable and for the period (2011-2015) before the implementation of (IFRS) (2016-2022) after the application of (IFRS)"and the (Springate) models to measure stability. Financial as an intermediary variable and the income model developed by Ohlson (1995) to measure the cost of capital as a dependent variable and to test the hypotheses, a statistical program (SPSS) was used. The results of our research show that there is a significant and inverse effect of the international standards variable on financial stability and that there is a significant direct effect of the standards on the increase in the cost of financing. There is an inverse effect of financial stability on the cost of financing in common stocks and there is no “impact of the international standards variable on the cost of financing through the role.” Mediator of the Financial Stability Variable. We conclude from the previous analysis that the adverse effect is due to the lack of financial stability in the majority of the sample banks. Accordingly, researchers recommend that companies be made aware of the importance of fully adopting IFRS standards and applying them correctly and effectively. In addition to increasing investment in developing capabilities and training employees to ensure the correct understanding and implementation of IFRS standards, monitoring and evaluating the adoption of IFRS standards, and analyzing their impact on financial stability and the cost of financing with common shares.